Sifat Ketahanan Api Lima Jenis Kayu dengan Pelapisan Carbon Phenolic Spheres (CPS) yang Diuji dengan Cone Calorimeter Fire Resistance Properties of Five Wood Species Laminated with Carbon Phenolic Spheres (CPS) Tested by Cone Calorimeter - Subyakto Subyakto; Wahyu Dwianto (Masyarakat Peneliti Kayu Indonesia, 2004)
In all aspects of wood utilization their fire resistance properties are very important; therefore efforts to enhance those properties are needed. In the previous study, graphite phenolic spheres (GPS) laminated on woods and plywood enhanced their fire properties. Carbon phenolic spheres (CPS) is a new material made from a mixture of wood char and phenolic resin, this material is cheaper than GPS. In the present experiment, CPS sheet was laminated on five wood species and their fire resistance properties were evaluated using cone calorimeter. The five wood species are randu (Bombax ceiba L.), angsana (Pterocarpus indicus Jacq.), mindi (Melia azedarach L.), puspa (Schima wallichii DC Korth), and mahoni (Swietenia mahagony L. Jacq). The specimen was 100 mm x 100 mm with thickness of 30 mm tested with cone calorimeter in accordance with ISO 5660 standard. Using cone calorimeter a homogenous heat was exposed to the surface of wood specimen, and ignited with igniter. About 1 mm thick of CPS sheet was laminated on the wood surface (100 mm x 100 mm). Specimen was tested at horizontal position and at heat flux of 40 kW/m2. On the unexposed wood surface, thermocouple was attached to measure increases of temperature. Results showed that five species of wood laminated with CPS have higher fire properties compared with control wood, however compared with woods laminated with GPS those results were lower.